4(x+1)-3(x-3)=25

Simple and best practice solution for 4(x+1)-3(x-3)=25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+1)-3(x-3)=25 equation:


Simplifying
4(x + 1) + -3(x + -3) = 25

Reorder the terms:
4(1 + x) + -3(x + -3) = 25
(1 * 4 + x * 4) + -3(x + -3) = 25
(4 + 4x) + -3(x + -3) = 25

Reorder the terms:
4 + 4x + -3(-3 + x) = 25
4 + 4x + (-3 * -3 + x * -3) = 25
4 + 4x + (9 + -3x) = 25

Reorder the terms:
4 + 9 + 4x + -3x = 25

Combine like terms: 4 + 9 = 13
13 + 4x + -3x = 25

Combine like terms: 4x + -3x = 1x
13 + 1x = 25

Solving
13 + 1x = 25

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 1x = 25 + -13

Combine like terms: 13 + -13 = 0
0 + 1x = 25 + -13
1x = 25 + -13

Combine like terms: 25 + -13 = 12
1x = 12

Divide each side by '1'.
x = 12

Simplifying
x = 12

See similar equations:

| -7x+3x^2+2=0 | | (x+4)2=81 | | 137=x+y | | 10x+12=112 | | -3x^2-2x+4=0 | | 4x+62=9x-13 | | 30-6x=3x+18 | | 10-6x=3x+18 | | =4x+15 | | -35-3x=9x+19 | | 130=2x-y | | -2(x+9)+91=13+24 | | 2(111)=d | | 7x+26=4x+77 | | 4x-6x=7 | | 34-2x=7x+21 | | -3x^2-4x+1=0 | | 3-8s=-29 | | 4x+y+x+3y=180 | | x^2-6x+9=2 | | 66x+35=25 | | (7-8)+17= | | 10x-28=4x+22 | | x^2=x+4 | | 97x+66=10 | | p(x)=-2x^2+60x-25 | | 169-2x=25x+22 | | 86x-53=9 | | 90-2x=4x+24 | | 4x^2+48x+27=0 | | y+9y+5=15 | | 60x-35=8 |

Equations solver categories